Nano-spectroscopic imaging of proteins with near-field scanning optical microscopy (NSOM) - Yong, Yang-Chun; Wang, Yan-Zhai; Zhong, Jian-Jiang (Current opinion in biotechnology, 2018)
[Display omitted] •Near-field scanning optical microscopy (NSOM) is promising for protein nanoimaging.•Spectroscopic NSOM opens up the possibility for single protein spectroscopy.•Advances and challenges in NSOM application in biotechnology are discussed. Understanding the hierarchical structure of proteins at their fundamental length scales is essential to get insights into their functions and roles in fundamental biological processes. Near-field scanning optical microscopy (NSOM), which overcomes the diffraction limits of conventional optics, provides a powerful analytical tool to image target proteins at nanoscale resolution. Especially, by combining NSOM with infrared (IR) or Raman spectroscopy, near-field nanospectroscopic imaging of a single protein is achieved. In this review, we present the recent technical progress of NSOM setup for nanospectroscopic imaging of proteins, and its application to nanospectroscopic analysis of protein structures is highlighted and critically reviewed. Finally, current challenges and perspectives on application of NSOM in emerging areas of industrial, environmental and medical biotechnology are discussed.